Assessment of knowledge, attitude, and practice towards pulmonary rehabilitation among COPD patients: A multicenter and cross-sectional survey in China. (November 2020) - Xie, Liang; Liu, Zilong; Hao, Shengyu; Wu, Qinhan; Sun, Lidan; Luo, Huixiu; Yu, Ronghuan; Li, Xia; Wu, Xiaodan; Li, Shanqun
Abstract: Background: Pulmonary rehabilitation (PR) has been recognized to be an evidence-based treatment recommended for chronic obstructive pulmonary disease (COPD). The aim of this study was to investigate COPD patients' knowledge, attitudes and practices towards PR in China. Methods: 1138 COPD patients from 13 hospitals were enrolled in this cross-sectional study. A questionnaire designed based on an official statement was completed by the participants. Effects of PR in patients were investigated. Results: Mean score of the knowledge portion was only 7.76, while 46.22% of the participants believed they needed PR. Attendance rate was 24.69%. Financial conditions and hospitalization were contributing factors for scores, attendance rate, and belief in demands for PR therapy. Severe pulmonary function impairment indicated more demands for PR (OR = 0.18) and higher uptake rate (OR = 0.30). There was a weak correlation between smoking status (rho = −0.060), diagnosis year (rho = 0.094), frequency of exacerbations (rho = 0.059) and grades. High CAT score is a facilitator for attitudes towards PR (OR = 0.022). 93.24% of patients claimed that their exercise tolerance improved with PR therapy. The improvements were positively associated with needs (rho = 0.20), family support (rho = 0.22), grades (rho = 0.18), and monthly income of the family (rho = 0.14), but negatively correlated with age (rho = −0.16), exacerbations (rho = −0.15), and CAT score (rho = −0.13). Conclusions: This study suggested poor perception, disbelief in the need for PR, and limited uptake of PR among COPD patients in China, and revealed the significant factors involved. The findings of this study may assist health professionals in developing targeted strategies to promote PR and improve access and uptake of PR. Highlights: This is the first study to uncover the current situation of PR therapy in China. Financial status and hospitalization were significant factors for patients' knowledge, attitudes and practices towards PR. Higher CAT score, being older and frequent exacerbations indicated fewer improvements of exercise tolerance. Family support was critical for gaining improvements from PR therapy.